In cell fluorescence activation and labeling of proteins mediated by FRET-quenched split inteins - Borra, Radhika (2012)
Methods to visualize, track and modify proteins in living cells are central for understanding the spatial and temporal underpinnings of life inside cells. Although fluorescent proteins have proven to be extremely useful for in vivo studies of protein function, their utility is inherently limited because their spectral and structural characteristics are interdependent. These limitations have spurred the creation of alternative approaches for the chemical labeling of proteins. We report in this work the use of fluorescence resonance emission transfer (FRET)-quenched DnaE split-inteins for the site-specific labeling and concomitant fluorescence activation of proteins in living cells. We have successfully employed this approach for the site-specific in-cell labeling of the DNA binding domain (DBD) of the transcription factor YY1 using several human cell lines. Moreover, we have shown that this approach can be also used for modifying proteins in order to control their cellular localization and potentially alter their biological activity.